(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Obesity and hyperlipidemia are two widespread and difficult health issues that affect people all over the world. In these situations, elevated blood lipid levels are risk factors for atherosclerosis, coronary artery disease, and cerebral vascular disease. The goal of the current investigation was to evaluate the phytoconstituents' inhibitory effects on in vitro HMG-CoA reductase, in vivo HFD-induced hyperlipidemia, and dexamethasone-induced hyperlipidemia. High cholesterol diet was prepared by mixing cholesterol 2%, sodium cholate 1% and coconut oil 2%, with powdered chow diet which was prepared as pellets was placed in the cage and administered for 20 days. Dexamethasone, a glucocorticoid excess is known to evoke plasma lipid elevation in the dose of 10 mg/kg/day, s.c. was administered to Wistar rats for 8 days. The in vitro assessment of HMG -CoA reductase activity indicated an IC50 value of 150 and 75 µg/mL by the extract and a standard drug (Pravastatin), respectively. Additionally, an in-silico evaluation was made using appropriate docking software and results also indicated as significant interactions of the identified compounds with the target enzyme. Treatment of rats with the ethanolic extract of Rhynchosia beddomei whole plant resulted in significant (p<0.05) reductions in total cholesterol, LDL cholesterol, VLDL cholesterol, and triglyceride. It can be illustrating that the methanolic extract of Rhynchosia beddomei whole plant contains potent bioactive phytocompounds might be inhibit HMG – CoA reductase and have reduction potential of atherogenic index.